Mortality and life expectancy of people with alcohol use disorder in Denmark, Finland and Sweden. (20th September 2014) - Westman, J.; Wahlbeck, K.; Laursen, T. M.; Gissler, M.; Nordentoft, M.; Hällgren, J.; Arffman, M.; Ösby, U.
<x xml:space="preserve">Abstract</x> Objective To analyse mortality and life expectancy in people with alcohol use disorder in Denmark, Finland and Sweden. Method A population‐based register study including all patients admitted to hospital diagnosed with alcohol use disorder (1 158 486 person‐years) from 1987 to 2006 in Denmark, Finland and Sweden. Results Life expectancy was 24–28 years shorter in people with alcohol use disorder than in the general population. From 1987 to 2006, the difference in life expectancy between patients with alcohol use disorder and the general population increased in men (Denmark, 1.8 years; Finland, 2.6 years; Sweden, 1.0 years); in women, the difference in life expectancy increased in Denmark (0.3 years) but decreased in Finland (−0.8 years) and Sweden (−1.8 years). People with alcohol use disorder had higher mortality from all causes of death (mortality rate ratio, 3.0–5.2), all diseases and medical conditions (2.3–4.8), and suicide (9.3–35.9). Conclusion People hospitalized with alcohol use disorder have an average life expectancy of 47–53 years (men) and 50–58 years (women) and die 24–28 years earlier than people in the general population.